PEMBERDAYAAN ANAK-ANAK PANTI ASUHAN PUTRI AISYIYAH BUKITTINGGI DALAM KETERAMPILAN “MEMBATIK” - Erfahmi Erfahmi; Irwan Irwan; Maltha Kharisma (Ranah Seni, 2018)
An orphanage is one of the means of protection and guidance for orphans, orphans and orphans and neglected children. This container is independent, which is sheltered under a foundation, one of which is Aisyiyah. The Aisyiyah Foundation provides facilities for sons and daughters with adequate facilities such as male and female dormitories, places of worship, sports and equipped with a well-organized management structure. In addition to formal activities that must be attended by orphanage children through school, it is also equipped with non-formal activities outside school hours which are more focused on efforts to equip children with several skills as a provision for them to be able to live independently in the midst of society. Besides providing skills for orphanage children is an effort to improve the quality of human resources (HR). One effort that can be done is to help orphanage children to develop skills in the field of textile crafts, namely batik with the application of traditional carving motifs on fashion products, table cloths, headscarves, paintings with a variety of shapes and sizes. This batik skill activity is very beneficial for orphanage children as a provision for them to become entrepreneurs later, if they are no longer the responsibility of the Foundation. To achieve the target as expected, this activity is carried out using the design, counseling, training and mentoring methods, so that each participant produces a product / work of Batik in the form of a table mat and wall decoration that has artistic value and is worth selling.